Camp Adventure; user based research and application in design - White, Amanda (Kansas State University, 2010)
Camp Adventure, a summer camp for the physically disabled, has obtained a site for the future Camp Adventure Conference and Retreat Center at Perry Lake, Ozawkie, Kansas. The camp serves youth and adults with cerebral palsy and spina bifida. Past rental facilities have been far from adequate for the camp’s basic needs of accessibility and has led the camp to seek a specially designed permanent home. As a counselor for 9 years, I have experienced firsthand the barriers and frustrations with inadequate facilities. Seeking to find solutions to the camp’s specific needs, I found William H. Whyte’s research methods and environmental psychology studies fitting to discover human preference and experiential qualities. To understand the best methods of adaptation, a series of user based research methods have been conducted to gather user input. The campers understand, from daily experience, what it takes to make an element or activity accessible, and their guidance will inform the design of select program elements. User input is not only being gathered from the camp, but from educational sources at Kansas State University, practicing professionals at Ochsner Hare and Hare, and local government representatives. Collaboratively molding the site’s existing form, the campers accessibility needs, and a complex program has created an exciting and challenging project. The program consists of 24 elements and activities, many of which are not traditionally handicap friendly. In-depth design studies and application of the user input has created the form and experience of seven program elements. This book contains literature and precedent studies, user based research results, the master plan for the entire site, and design details of seven program elements. It is to be used by Camp Adventure as a guide to implementation of the camp design. It is the path for Camp Adventure to achieve their dream: a barrier free, fully accessible, adventure; Camp Adventure.
Keywords: Camp; Physically disabled; Cerebral palsy; Spina bifida; User-based research methods; Adaptive methods; Landscape Architecture (0390); Psychology, Behavioral (0384); Sociology, Individual and Family Studies (0628)